BATTLING THE UNSEEN: NURSES' COPING MECHANISMS IN THE ERA OF COVID-19 - Alexandra , Dimitriou Papadopoulos; Maria , Ioannou Georgiou; Constantinos , Nikolaou Papadakis (Research Journal of Health, Medicine and Nursing, 2024)
In February 2020, the World Health Organization (WHO) declared the outbreak of a new coronavirus disease, COVID-19, as a Public Health Emergency of international concern, raising the alarm about its potential global spread. Shortly after, in March 2020, WHO officially characterized COVID-19 as a pandemic? This novel disease was named "COVID-19," while the virus itself was named "severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)" due to its genetic relationship with the 2003 SARS coronavirus outbreak. This distinction is crucial, as the two viruses, despite their relatedness, exhibit distinct characteristics. This paper highlights the nomenclature and taxonomy of the virus, emphasizing the significance of precise terminology in understanding and addressing the ongoing global health crisis